KEMITRAAN WORLD WRESTLING ENTERTAINMENT (WWE) DAN GIRL UP DALAM MEMBERDAYAKAN OLAHRAGA PEREMPUAN MELALUI SPORT FOR A PURPOSE - Zahrhin Bunga Syazdwina; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
WWE was a global wrestling corporation that operated in the entertainment industry. In WWE, women wrestlers received unequal airtime, pay, and pay-per-view participation. The hashtag #GiveDivasAChance became popular in 2015 after a 30-second match between female wrestlers ignited the Twitter community. As Chief Brand Officer (CBO), Stephanie McMahon responded to audience feedback by empowering WWE women through Women Evolution. This research implied a constructivist viewpoint and a group analysis level. Utilizing secondary data collection techniques, literature, documents, and video observations published on the WWE channel, as well as video interviews with WWE female competitors, a qualitative research method was employed. This study showed that the value of women in WWE had changed. With the introduction of Women Evolution, which was being implemented in stages, the role of female wrestlers expanded, as evidenced by their participation in pay-per-view events. WWE collaborated with Girl Up, a global leadership development initiative founded in 2010 by the United Nations Foundation, to alter the perception of WWE women. WWE and Girl Up collaborated to create the Sport for a Purpose program, which sought to empower women in sports worldwide. Keywords : WWE, Girl Up, Equality, Gender, Women Evolution.